Preliminary results from digestive adaptation: a new surgical proposal for treating obesity, based on physiology and evolution - Santoro, Sérgio; Velhote, Manoel Carlos Prieto; Malzoni, Carlos Eduardo; Milleo, Fábio Quirino; Klajner, Sidney; Campos, Fábio Guilherme (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Most bariatric surgical techniques include essentially non-physi- ological features like narrowing anastomoses or bands, or digestive segment exclusion, especially the duodenum. This potentially causes symptoms or complications. The aim here was to report on the preliminary results from a new surgical technique for treating morbid obesity that takes a physiological and evolutionary approach. DESIGN AND SETTING: Case series description, in Hospital Israelita Albert Einstein and Hospital da Polícia Militar, São Paulo, and Hospital Vicentino, Ponta Grossa, Paraná. METHODS: The technique included vertical (sleeve) gastrectomy, omentectomy and enterec- tomy that retained three meters of small bowel (initial jejunum and most of the ileum), i.e. the lower limit for normal adults. The operations on 100 patients are described. RESULTS: The mean follow-up was nine months (range: one to 29 months). The mean reductions in body mass index were 4.3, 6.1, 8.1, 10.1 and 10.7 kg/m2, respectively at 1, 2, 4, 6 and 12 months. All patients reported early satiety. There was major improvement in comorbidities, especially diabetes. Operative complications occurred in 7% of patients, all of them resolved without sequelae. There was no mortality. CONCLUSIONS: This procedure creates a proportionally reduced gastrointestinal tract, leaving its basic functions unharmed and pro- ducing adaptation of the gastric chamber size to hypercaloric diet. It removes the sources of ghrelin, plasminogen activator inhibitor-1 (PAI-1) and resistin production and leads more nutrients to the distal bowel, with desirable metabolic consequences. Patients do not need nutritional support or drug medication. The procedure is straightforward and safe.